FINANCIAL LITERACY AMONG UNIVERSITY STUDENTS: EMPIRICAL EVIDENCE FROM INDONESIA - I Wayan Nuka Lantara; Ni Ketut Rai Kartini (Faculty of Economics and Business, Universitas Gadjah Mada, 2015)
This study investigates the level of financial literacy among undergraduate and graduate students. The study also examines the association between the students’ demographic factors and their financial literacy rate. Data were collected by distributing 800 questionnaires to undergraduate and graduate students of Gadjah Mada University, Indonesia, covering cross educational majors, ages, gender, education levels, marital status, income, and work experience. Out of the sample, a total of 348 respondents returned completed questionnaires, which gave a response rate of 43.5 percent. The findings show that on average 45.39 percent of the respondents answered the questions correctly, which is relatively low compared to what other studies found in other countries, such as Chen and Volpe (1998) in the US (52.87 percent), or Beal and Delpachitra (2003) in Australia (53 percent). It also seems that male students, students with economics and business majors, those with higher incomes, and more work experience have a higher financial literacy rate. Using probit and tobit regression tests, the study revealed that education levels and academic disciplines are positively associated with the financial literacy rate.Keywords: financial information, literacy rate, education, finance, Indonesia